Liquid Crystals Recent Advancements in Fundamental and Device Technologies - Kumar Choudhury, Pankaj (IntechOpen, 2018)
Liquid crystals exhibit amazingly interesting properties that make them indispensable for several technological applications. The book Liquid Crystals - Recent Advancements in Fundamental and Device Technologies is aimed to focus on various aspects of research and development that liquid crystal mediums have come across in recent years. This would be ranging from the physical and chemical properties to the important applications that the liquid crystals have in our everyday life. It is expected that the book will make the expert researchers to be abreast of recent research advancements, whereas the novice researchers will benefit from both the conceptual understanding and the recent developments in the area. Multitudes of research themes and directions pivoted to liquid crystals remain the essence, which the readers would get the glimpse of and move ahead for further investigations.